2018
DOI: 10.1155/2018/6313484
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Mechanism of TLR9/KLF4 in FFA-Induced Adipocyte Inflammation

Abstract: Objective Current research has reported that obesity is a chronic inflammatory state, which is closely related with excessive accumulation of free fatty acid, while the specific mechanism that high level of FFA causes inflammation is not very clear. Thus, our research intended to observe the high FFA effects on TLR9/KLF4 expression and the downstream inflammatory factors, to explore the mechanism of inflammatory response suppressed by TLR9/KLF4. Methods qRT-PCR and Western blot were used to detect the mRNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Wang et al conducted a study on omental adipocytes culture, rat models but also on humans [22]. In obese persons the mRNA expression levels of KLF4 were significantly lower than in the normalweight subjects and they significantly and negatively correlated with BMI, TG, and TNF-α [22]. These results are contradictory to our own ones, however they evaluated the mRNA expression of KLF4 not serum level and the study groups were totally different.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Wang et al conducted a study on omental adipocytes culture, rat models but also on humans [22]. In obese persons the mRNA expression levels of KLF4 were significantly lower than in the normalweight subjects and they significantly and negatively correlated with BMI, TG, and TNF-α [22]. These results are contradictory to our own ones, however they evaluated the mRNA expression of KLF4 not serum level and the study groups were totally different.…”
Section: Discussionmentioning
confidence: 64%
“…Comparison between KLF4 concentrations depending on BMI before and after treatment and controls KLF4 induced by obesity. Wang et al conducted a study on omental adipocytes culture, rat models but also on humans [22]. In obese persons the mRNA expression levels of KLF4 were significantly lower than in the normalweight subjects and they significantly and negatively correlated with BMI, TG, and TNF-α [22].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression level of APN, specifically secreted by adipocytes, was significantly inhibited although the number of adipocytes was increased. We previously reported that APN expression was lower in adipose tissue of obese individuals, and palmitic acid inhibits APN expression in 3T3‐L1 adipocytes 36 . Reports in the literature have described how FAs, in addition to their role as bioenergetic sources, can also act as extracellular signaling molecules: FAs may affect different signaling pathways crucial to the biological functions of tumor cells, such as proliferation and invasion 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, KLF4 suppresses the proinflammatory differentiation of renal infiltrating macrophages and attenuates kidney injury and fibrosis by inhibiting myeloid cell generation of TNF-α [33]. Upregulation of KLF4 in mature adipocytes inhibited the expression of the inflammatory factors P65, TNF-α, IL-1β, and monocyte chemoattractant protein 1 and promoted the expression of the anti-inflammatory factor APN [34]. Studies have also shown that KLF4 may be involved in the pathogenesis of inflammatory bowel disease and esophageal epithelial inflammation by regulating the NF-κB signaling pathway [35,36].…”
Section: Statement Of Ethicsmentioning
confidence: 99%